Investment decision and methodology: Keynes and neoclassical - Crocco, Marco (Estudos Econômicos (São Paulo), 1998)
The aim of this paper is, in analysing the investment decision, to show how methodological differences can determine differences in the theories and statements about economic events. Two views were chosen, Keynes and neoclassical, and theoretical and methodological comparisons were made. These allowed the author to conclude that there is a direct relationship between the methodology used by each school of thought and its understanding of the investment process. The paper is structured in five sections. In the first two, the two investment theories are briefly presented. In section three, a theoretical comparison is made aiming to clarify the most important differences. In section four, it is shown that underlying the theoretical differences between the two schools of thought, there is a deeper methodological difference, in such a way that the latter determines the former. Finally, some conclusions are drawn, showing how the methodological differences dictate the theoretical statements.